Palladium mediated deallylation in fully aqueous conditions for native chemical ligation at aspartic and glutamic acid sites. Issue 22 (16th May 2018) - Jbara, Muhammad; Eid, Emad; Brik, Ashraf
Abstract : An efficient native chemical ligation approach at Asp and Glu sites is reported applying a hydrazide precursor, as a peptide thioester, and allyl protection at the side chain of Asp and Glu. Abstract : An efficient native chemical ligation approach at Asp and Glu sites is reported applying a hydrazide precursor, as a peptide thioester, and allyl protection at the side chain of Asp and Glu. The allyl protection was efficiently removed, after the ligation step, using the water-soluble palladium complex [Pd(allyl)Cl]2 and glutathione within a few minutes under fully aqueous conditions.